Thermal energy transfer around buried pipe infrastructure. (March 2022) - Shafagh, I.; Shepley, P.; Shepherd, W.; Loveridge, F.; Schellart, A.; Tait, S.; Rees, S.J.
Abstract: Decarbonisation of heating is essential to meet national and international greenhouse gas emissions targets. This will require adoption of a range of solutions including ground source heat pump and district heating technologies. A novel route to these solutions includes dual use of buried infrastructure for heat transfer and storage in addition to its primary function. Water supply and wastewater collection pipes may be well suited for thermal energy applications being present in all urban areas in networks already in proximity to heat users. However, greater understanding of their potential interactions with surrounding heat sources and sinks is required before full assessment of the energy potential of such buried pipe networks can be obtained. This paper presents an investigation into the thermal interactions associated with shallow, buried water filled pipes. Using the results of large scale experiments and numerical simulation it is shown that soil surface ambient conditions and adjacent pipes can both act as sources or sinks of heat. While conduction is the main mechanism of heat transfer in the soil directly surrounding any pipe, any adjacent water filled pipes may lead to convection becoming important locally. In the test case, the thermal sphere of influence of the water filled pipe was also shown to be large, at in excess of 4 m over a timescale of 4 months. Taken together, these points suggest that design and analysis approaches when using water supply and wastewater collection networks for heat exchange and storage need careful consideration of environmental interactions, heat losses and gains to adjacent pipes or other infrastructure, and in ground conditions for a number of pipe diameters from any buried pipe. Highlights: A 30 m long buried pipe was thermally activated by forced convection with hot water. The pipe had a thermal influence extending over 4 m (¿30Dpipe ) after 4 months. Ambient conditions and adjacent pipes interact thermally with the buried water pipe. Fluid in adjacent pipes can act as a heat sink due to induced convection. Thermal diffusion dominates in the low moisture content sand around the pipe.